JavaScript best practices - Hooper, Brett; Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2017)
"Any IT professional or casual developer anticipating a better understanding of the JavaScript language and it's commonly used design patterns and structures needs to go through this course and absorb all of its content. Anyone desiring to learn more about the language and better ways to use it needs the knowledge, demonstrations, and practice presented in this course. This not only includes web, mobile, and service application developers, but also architects, UI designers, testers, and administrators. This course provides a well-curated collection of JavaScript concepts that are generally unknown or overlooked and have significant impact on overall JavaScript code quality."--Resource description page.
Presenter, Brett Hooper.
Title and publication information from resource description page (Safari, viewed October 2, 2017).
Presenter's name from resource description page.
Keywords: JavaScript (Computer program language); Application software -- Development; Web site development; Electronic books